Schulenkorf, N. et al. (eds). Handbook of Sport and International Development. Editorial Edward Elgar Publishing Limited, Glos, 2022, 462 páginas. - Augusto Rembrandt Rodríguez Sánchez (Universidad Pablo de Olavide, 2024)
Recensión de la obra de Schulenkorf, N. et al. (eds). Handbook of Sport and International Development. Editorial Edward Elgar Publishing Limited, Glos, 2022, 462 páginas.